Expression of clock genes period and timeless in the central nervous system of the Mediterranean flour moth, Ephestia kuehniella - Kobelková, Alena; Závodská, Radka; Sauman, Ivo; Bazalová, Olga; Dolezel, David (Journal of biological rhythms, 2015)
Homologous circadian genes are found in all insect clocks, but their contribution to species-specific circadian timing systems differs. The aim of this study was to extend research within Lepidoptera to gain a better understanding of the molecular mechanism underlying circadian clock plasticity and evolution. The Mediterranean flour moth, Ephestia kuehniella (Pyralidae), represents a phylogenetically ancestral lepidopteran species. We have identified circadian rhythms in egg hatching, adult emergence, and adult locomotor activity. Cloning full-length complementary DNAs and further characterization confirmed one copy of period and timeless genes in both sexes. Both per and tim transcripts oscillate in their abundance in E. kuehniella heads under light-dark conditions. PER-like immunoreactivity (PER-lir) was observed in nuclei and cytoplasm of most neurons in the central brain, the ventral part of subesophageal complex, the neurohemal organs, the optic lobes, and eyes. PER-lir in photoreceptor nuclei oscillated during the day with maximal intensity in the light phase of the photoperiodic regime and lack of a signal in the middle of the dark phase. Expression patterns of per and tim messenger RNAs (mRNAs) were revealed in the identical location as the PER-lir was detected. In the photoreceptors, a daily rhythm in the intensity of expression of both per mRNA and tim mRNA was found. These findings suggest E. kuehniella as a potential lepidopteran model for circadian studies.
Keywords: Optic Lobe, Nonmammalian; mozek; PER-like immunoreactivity; cirkadiánní rytmus; circadian clock; messenger RNA; světlo; In Situ Hybridization; regulace genové exprese; Sequence Analysis, DNA; hybridizace in situ; eclosion rhythm; hmyzí proteiny; Female; fotoperioda; Phenotype; jaderné proteiny; DNA, Complementary; komplementární DNA; zvířata; Immunohistochemistry; zrakový lalok nesavčí; imunohistochemie; Biological Clocks; Light; klonování organismů; Circadian Rhythm; sekvenční analýza DNA; RNA, Messenger; Circadian Clocks; activity rhythms; ženské pohlaví; Gene Expression Regulation; Insect Proteins; Male; timeless; Brain; fenotyp; Moths; Nuclear Proteins; můry; Photoperiod; Lepidoptera; biologické hodiny; cirkadiánní hodiny; Animals; mužské pohlaví; cirkadiánní proteiny Period; Cloning, Organism; Period Circadian Proteins